193 Lack of Fibroblast Growth factor-23 (FGF23) Preserves Cardiac Function in a Murine Model of Acute Myocardial Infarction. (3rd June 2016) - Ford, Kristopher; Slavic, Svetlana; Zeitz, Ute; Dolezal, Marlies; Erben, Reinhold G; Andrukhova, Olena
Abstract : Myocardial infarction (MI) is a major cause of death worldwide. We recently showed that intact circulating fibroblast growth factor-23 (FGF23) is profoundly up-regulated after experimental MI in mice and rats. FGF23 is a bone-derived hormone involved in systemic phosphate homeostasis and vitamin D metabolism. Although the pathophysiological mechanisms remain to be identified, clinical studies have shown a strong association between FGF23 and left ventricular hypertrophy, atrial fibrillation and cardiac systolic dysfunction. Here, we explored the hypothesis that FGF23 may be causally linked to progression of cardiac dysfunction post-MI, using a mouse model lacking both Fgf23 and a functioning vitamin D receptor (VDR). Surgery was performed on 3-month-old, male, wild-type (WT), VDR and Fgf23 -/- /VDR Î"/Î" (Fgf23/VDR) compound mutant mice on a C57BL/6 background. To normalise mineral homeostasis in VDR-ablated mice, all mice were kept lifelong on a rescue diet enriched with calcium, phosphorous and lactose. MI was induced by permanent ligation of the left descending coronary artery. Sham-operated (Sham) mice served as a control. One week after MI, cardiac function was assessed by echocardiography and electrocardiography (ECG). Intracardial pressure monitoring was performed by catheterization as a terminal procedure, 2 weeks post-MI. Echocardiography confirmed left ventricular infarction, and ECG recordings revealed comparable ST depression in MI mice of all genotypes. However, Fgf23/VDR compound mutant MI mice showed improved fractional shortening, relative to WT and VDR MI controls. In addition, Fgf23/VDR compound mutant MImice were more resistant against the impairment of ventricular contraction and relaxation observed in WT and VDR MI mice, as measured by left ventricular dP/dtmax, dP/dtmin, and relaxation time tau, 2 weeks post-MI surgery. Our data indicate that lack of Fgf23 improves cardiac contractile function following experimental MI. This finding underscores the potential importance of the heart-bone-axis and of the new field of cardio-osteology  because the levels of circulating intact FGF23 may influence cardiac recovery after MI.